2018
DOI: 10.1021/acsenergylett.8b01540
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Node Metal–Organic Frameworks as Efficient Electrocatalysts for Oxygen Evolution Reaction

Abstract: Metal organic frameworks (MOFs), an emerging class of nanoporous crystalline materials, have become increasingly attractive for solar energy applications. In this work, we report a newly designed mixed-node MOF catalyst, Co x Fe1–x -MOF-74 (0 < x ≤ 1), which acts as a highly efficient electrocatalyst for oxygen evolution reaction (OER) in alkaline solution with remarkably low overpotential (280 mV at a current density of 10 mA/cm2), small Tafel slope (56 mV/dec), and high faradic efficiency (91%) and can deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
160
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(176 citation statements)
references
References 43 publications
16
160
0
Order By: Relevance
“…When increasing the Fe content, the PXRD patterns of the Ni 10−x Fe x ‐CPs (Figure S1b,c, Supporting Information) still agree with the initial host crystal structure, while exhibiting a peak shift to lower angles at around 2θ ≈ 9.3°, suggesting the successful incorporation of Fe into the Ni‐CP lattice. [ 27 ] The structural functional groups and coordination environments of the Ni 10−x Fe x ‐CP samples were further corroborated by FTIR and Raman spectroscopy (Figures S2 and S3, Supporting Information). The obtained results demonstrated that the vibrational signature of Ni 10−x Fe x ‐CP samples did not significantly change, while some main vibration modes (e.g., M‐NC‐Ni) displayed a shift to lower wavenumbers due to the substitution of Ni by Fe.…”
Section: Resultsmentioning
confidence: 79%
“…When increasing the Fe content, the PXRD patterns of the Ni 10−x Fe x ‐CPs (Figure S1b,c, Supporting Information) still agree with the initial host crystal structure, while exhibiting a peak shift to lower angles at around 2θ ≈ 9.3°, suggesting the successful incorporation of Fe into the Ni‐CP lattice. [ 27 ] The structural functional groups and coordination environments of the Ni 10−x Fe x ‐CP samples were further corroborated by FTIR and Raman spectroscopy (Figures S2 and S3, Supporting Information). The obtained results demonstrated that the vibrational signature of Ni 10−x Fe x ‐CP samples did not significantly change, while some main vibration modes (e.g., M‐NC‐Ni) displayed a shift to lower wavenumbers due to the substitution of Ni by Fe.…”
Section: Resultsmentioning
confidence: 79%
“…The layered double hydroxides (LDH) with unique structure, abundant interstratified electrons and channels for intermediate adsorption and desorption display wonderful water splitting performance 17–20. Additionally, the metal–organic frameworks (MOFs) and their based nanocrystals as newly nanomaterials have got much attention in various fields, but their structure limited the active sites exposure for the complete coordinative metal sites 21–25. Therefore, it is important to enable the cost‐effective, large‐scale production of these catalysts, and further improve the performance and efficiency of overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the obtained catalyst CoFeNi@CNTs delivered a low overpotential of 287 mV to achieve 10 mA cm À 2 and a small Tafel slope of 32 mV dec À 1 , obviously superior to the commercial IrO 2 and most previous reported catalysts. [34][35][36][37][38] The CoFeNi@CNTs also exhibit excellent OER stability with small current density decay after 12 h.…”
Section: Introductionmentioning
confidence: 98%